Effect of Trovafloxacin on Production of Cytokines by Human Monocytes - Khan, Anis A. (American Society for Microbiology, 1998)
Antibiotics have previously been shown to have immunomodulatory effects. We examined the effect of the broad-spectrum fluoroquinoline antibiotic trovafloxacin on cytokine synthesis by monocytes obtained from healthy human volunteers and stimulated with either lipopolysaccharide or gram-positive cells (heat-killed Staphylococcus aureus [Pansorbin]). Trovafloxacin levels achievable in humans suppressed in vitro synthesis of each of the cytokines analyzed, viz., interleukin-1α (IL-1α), IL-1β, IL-6, IL-10, granulocyte-macrophage colony-stimulating factor, and tumor necrosis factor alpha. This effect was not due to direct effects of the drug on cellular viability; at these concentrations, trovafloxacin did not have demonstrable cytotoxicity for the monocytes, as determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide (MTT) assay. Although similar patterns of suppression of cytokine synthesis were observed in samples obtained from the same volunteers on different days, there were significant day-to-day variations. These results reveal that trovafloxacin possesses significant immunomodulatory activity in vitro and suggest that suppression of acute-phase inflammatory responses may occur in vivo, elicited through trovafloxacin’s effect on cytokine synthesis by human monocytes.